The relationship between attentional bias, anxiety sensitivity and metacognitive beliefs in substance abuser: with an emphasis on mediating effects of emotion regulation strategies - Dabaghi, Parviz; Fahimi, Samad; Rahimkhanli, Masoumeh; Taghva, Arsia; Azimi, Zeynab (International Journal of Applied Behavioral Sciences, 2015)
Background: Several studies have shown that Attentional Bias plays a role in the beginning, persistence and relapse of Substance Abuse Disorder. Therefore, identifying the factors related to Attentional Bias in Substance Abusers is important. In so doing, the present study was aimed at examining the relationship between attentional bias, Anxiety Sensitivity and Metacognitive Beliefs in Substance Abusers with an emphasis on mediating effects of Emotion Regulation Strategies. Methods: The present study is fundamental in terms of the objective and descriptive regarding data collection which was conducted within the framework of a correlation study. The statistical universe comprised a group of soldiers in Tehran who were considered as Substance Abusers and had been referred to Addiction Treatment Centers of Baharestan County. Among the statistical universe, 120 participants were selected by non-random purposive sampling. Finally, Anxiety Sensitivity, Metacognitive Beliefs, Emotional Regulation Strategies and the Stroop test questionnaires were conducted on the sample. For sorting, processing and analysis of data and the evaluation of the research hypothesis, we used the SPSS and LISREL. To examine the relationship between variables, the Pearson correlation and path analysis were used. Results: Pearson correlation results indicated that Anxiety Sensitivity, Metacognitive Beliefs, Suppression, and Reappraisal have a significant relationship with the Attentional Bias.The results of the path analysis revealed that the direct effect of Anxiety Sensitivity and Metacognitive Beliefs on the Attentional Bias is not significant, but these structures may have an effect on the Attentional Bias only through the mediator variables (Suppression and Reappraisal). Conclusion: An individual resorts to metacognitive beliefs to get rid of the negative emotions caused by high Anxiety Sensitivitybut these emotions get intensified in this process and the individual in the long term experiences Substance Abuse through avoidance strategies such as Suppression.Therefore, whenthe personexperiences negative emotions, he will have an Attentional Bias toward liberating signs of Substance Abuse inside and outside.